Economic implications of different cork oak forest management systems - Pinheiro, António C. (2010)
The agro-silvopastoral system 'montado' is mostly dominated by Mediterranean evergreen oaks such as, cork oak (Quercus suber L.) and holm oak (Quercus rotundifolia). The 'montado' production system management aims the maintenance of a balanced sustainable land use to cope with the Mediterranean climate variability. One important issue in cork oak forests is the control shrub growth in order to prevent forest fire hazard, which is of high risk in Mediterranean climate. In this article, two shrub control systems are compared and the results show that although soil disking is more profitable than shrub cutting, the results are reversed, if one considers the carbon sequestration. This means that besides the great economic sustainability of cork oak dependence on the price of cork, the profitability of different shrub control methods depend also on the way society valuates other goods and services provided by cork oak forest.